Pharmacogenomics - A Boon For Chronic Diseases - JYOTI DUA; ALANKAR GUPTA; KRITI PACHAURI; SHIRISH DEWANGAN (International Journal of Pharma and Bio Sciences, 2011)
As the health care industry is showing diversification and is attempting to offer solution to the masses. There has been a rapid advancement in the field of research and development such as enabling techniques like gene therapy, microarray testing, MALDI TOF, pharmacoinformatics and pharmacogenomics. The current health care scenario is taking into account the genetic make-up for each individual and is distinctly more towards “trial-and-error” methodology, which subjects the case and their physician to higher probability of uncertainty of outcome. The unturned milestones of several drugs like Rezulin, Baycol and Fen-phen have provided with a lesson and ways to test prospective drugs, for toxicity. Lately, customized therapy is playing the key role in health care and diagnostic industry. Pharmacogenomics gives the new definition to the ways drugs are developed, selection of the drugs to the patient; based on their genetic make-up. Pharmacogenomics use genomic and sequence data host and pathogens to identify potential drug target. This field heavily depends on bioinformatics. By the definition, despite its- genomic suffix, pharmacogenomics is not limited to analysis of Deoxyribonucleic Acid (DNA), but rather also includes Ribonucleic Acid (RNA) and protein This paper deals with the efficacy of the technique, its relevance to the Indian market and its cost parameter in the developing country. The paper deals with basic concept of pharmacogenomics, role in drug development, its .limitations, ethical issues related to it and its need in the Indian as well as global market with special reference to chronic diseases such as Alzheimer’s disease, colorectal cancer which is common to both the sexes globally and AIDS, the disease most discussed from approximately three decades.